Anti-Oxidant, Anti-Inflammatory and Antinociceptive Properties of the Acetone Leaf Extract of Vernonia Amygdalina in Some Laboratory Animals - Adeolu Alex Adedapo; Olujoke Janet Aremu; Ademola Adetokunbo Oyagbemi (Tabriz University of Medical Sciences, 2014)
Purpose: Vernonia amygdalina is a medicinal plant of great importance that has its fresh leaves rich in vitamins and salt hence, it is valuable in human diet. The anti-oxidant, anti-inflammatory and analgesic activities of its acetone leaf extract were evaluated in this study to validate its folkloric use. Methods: The acetone extract is prepared by dissolving ground plant materials (200g) in 1 L of acetone for 48 h, filtered, and then dried using rotary evaporator before it is used for the pharmacological investigations. Standard phytochemical methods were used to test for the presence of phytoactive compounds in the plant. Acute toxicity was carried out in mice to determine safe doses for use. The anti-inflammatory activities were conducted using carrageenan and histamine to induce oedema in rats while analgesic activities were embarked upon using acetic acid- induced writhing test and formalin-induced paw lick test. The anti-oxidant activities were assessed in vitro using ABTS, DPPH, FRAP and total polyphenolics. Results: The results from this study showed that the 100 and 200 mg/kg doses of the acetone extract caused significant reduction in oedema induced by both carrageenan and histamine. Similar effect was observed in analgesic tests which were comparable to that of indomethacin, the reference drug used in the study. Conclusion: The anti-oxidant effects were also good and the pharmacological activities may be due to the presence of polyphenols and other phytochemicals contained in the plant. The study may have thus validated the folkloric use of this plant as a medicinal and nutritional agent.